Transdiagnostic considerations are critical to understanding childhood neurodevelopmental disorders - Hoza, Betsy; Shoulberg, Erin K. (Frontiers in Human Neuroscience, 2024)
Growing dissatisfaction with the current categorical diagnostic systems has led to a movement toward transdiagnostic dimensional approaches to assessment of childhood mental health disorders. We argue that a transdiagnostic approach is especially important and appropriate when screening for neurodevelopmental disorders during early childhood. In the early childhood years, symptoms often appear in the form of developmental delays that could portend a variety of different disorders. Early intervention at this point is critical, even though a final endpoint disorder is not yet apparent. Intervening early has the potential to grow the area of weakness, possibly correcting or at least ameliorating these delays. Early intervention requires a multidisciplinary approach integrating efforts across settings and providers that monitor the development of young children. We argue here that young children's language ability is central to the development of social cognition, and a prerequisite for adequate social functioning. Social deficits are defining features of a subset of neurodevelopmental disorders such as autism spectrum disorder and social (pragmatic) communication disorder. Critically, impairment in social functioning is common in additional neurodevelopmental disorders such as attentiondeficit/hyperactivity disorder (ADHD), learning disorders, and even motor disorders. For this reason, we argue that, at the earliest sign of a possible neurodevelopmental disorder, children should be screened for language deficits prior to initiating a focused assessment for a specific type of neurodevelopmental disorder such as ADHD. Any detected language deficits should be considered in the design and implementation of the assessment, as well as the ultimate intervention plan.